Tingkat Adopsi Petani Terhadap Benih Unggul Padi Sawah Di Kabupaten Aceh Besar Provinsi Aceh - M Masyitah; A Agussabti; Suyanti Kasimin (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2019)
The research aims to analyze the farmers’ perception of qualified seed in Aceh Besar regency, the factors that influenced the farmers’ perception of qualified seed and relationship between the farmers’ perception and adoption level of qualified seed in Aceh Besar regency. This research hypothese used a quantitative descriptive method. The respondents are 51 farmers taken from six villages in four subdistricts in Aceh Besar regency. The unit analysis consisted of four subdistricts in Aceh Besar regency with 51 respondents. The results obtained that (1) respondents have a good perception about a qualified seed, (2) the ages, educational backgrounds, the wide of lands, status of lands, and experiences were the internal factors that influenced the farmers’ perception of a qualified seed, (3) adopted level of farmers’ perception was high meanwhile adoption of innovation of respondents was classified into early majority